A decomposition of inequality and poverty changes in the context of macroeconomic adjustment: A microsimulation study for Côte d'Ivoire - Michael Grimm (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper proposes a microeconomic decomposition of the evolution of income inequality in Côte d'Ivoire in the 1990s, allowing the in-depth analysis of simultaneous contributions of four types of phenomena to the evolution of the distribution of income: a change in the remuneration rates of observed and unobserved earnings determinants, a change in occupational preferences, and a change in the sociodemographic population structure. I show, for instance, that the increase in income inequality in Abidjan was the result of changes in the sociodemographic population structure and of changes in unobserved earnings determinants, even though higher activity, inflows in wage labour, a drop in returns to schooling, and the Ivorian/non-Ivorian wage differential worked toward a more equal distribution. Concerning the link between growth and inequality, it is interesting to note that both negative income growth in Abidjan as well as positive income growth in rural Côte d'Ivoire, were connected with rising inequality. – decomposition ; income distribution ; microsimulation ; poverty ; Côte d'Ivoire
Keywords: C15; D31; J22; J31; O12; 330; Einkommensverteilung; Armut; Dekompositionsverfahren; Elfenbeinküste